High contents of proline and anthocyanin increase protective response to salinity in Oryza sativa L. spp. indica - Chutipaijit, Sutee; Cha-um, Suriyan; Sompornpailin, Kanokporn (My University, 2011)
Pigmented rice cultivar is a good candidate for abiotic tolerance especially salt tolerant trait. Physiological and growth parameters of eight indica rice genotypes under control or salt stress conditions were subjected to Hierarchical cluster analysis. From cluster ranking, rice genotypes were classified into two groups, salt-tolerant (Sangyod, Khao Dang, Kulab Dang and TD49) and salt-sensitive genotypes (Klum Sakol, Klum Khonkaen1, Klum Khonkaen2 and Black Sticky Rice). In salt stress (100 mM NaCl), the salt-tolerant genotypes showed the high percentages of proline and anthocyanin more than in the salt-sensitive genotypes. In addition, the photosynthetic pigment stabilizations of stressed-seedlings were positively correlated to the proline (R 2 = 0.98) and anthocyanin (R 2 = 0.70) accumulations. While, the malondialdehyde (MDA) contents of salt-stressed seedlings were negatively correlated to the proline (R 2 = 0.63) and anthocyanin (R 2 = 0.51) accumulations. Moreover, the total antioxidant activity of extraction from stressed-seedlings was assessed using the ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) method. The higher percentages of total antioxidant activity were determined in salt-tolerant (125-199%) than salt-sensitive genotypes (106-113%). From the results it can be concluded that accumulation of above mentioned metabolites is associated with cellular protection and salt detoxification in salinity rice seedlings.
Keywords: Anthocyanin; Indica rice; Lipid peroxidation; Photosynthetic pigments; Proline; Salt stress